005.3 Multiplex real-time pcr with high resolution melting analysis for detecting resistance mechanisms in neisseria gonorrhoeae. (13th September 2015) - Dona, V; Low, N; Guilarte, YN; Lupo, A; Furrer, H; Unemo, M; Endimiani, A
Abstract : Background: Molecular tests to detect antimicrobial resistance in Neisseria gonorrhoeae (NG) are urgently needed. Genetic methods are the mainstay of NG detection in many settings, but resistance testing still requires conventional phenotypic tests. The objective of this study was to develop an assay to detect the most clinically important genetic markers conferring resistance to antibiotics used for the treatment of gonorrhoea. Methods: We designed a fluorescent dye real-time PCR assay combined with high resolution melting (HRM) analysis. Several triplex and duplex reactions included target sequences for: two NG-specific genes ( porA and opa ); targets specific for the penA mosaic XXXIV (A501, G545S), associated with reduced cephalosporin susceptibility; single nucleotide polymorphisms conferring resistance to ciprofloxacin (GyrA S91F), azithromycin (23S rRNA A2059G and C2611T) and spectinomycin (16S rRNA C1192T and 5S rRNA T24P). We tested >50 characterised NG isolates, including: clinical isolates resistant to ciprofloxacin, azithromycin, spectinomycin, ceftriaxone (strain F89), strains with reduced cephalosporin susceptibility, the wild-type reference strain ATCC49226, and commensal Neisseria spp. Results: HRM analysis correctly identified: all NG strains and all mutations, except for the A501P mutation in strain F89. However, cross-reactions with commensal Neisseria spp. occurred for: penA mosaic XXXIV (n = 3 species) and 23S rRNA (n = 3 species). Conclusion: Our multiplex PCR assay accurately identified NG and detected the most frequent mutations associated with antimicrobial resistance in cultured isolates. The assay provides results significantly quicker than current culture-based methods. The analytical sensitivity and specificity of the assay for use with urethral, rectal, pharyngeal and vaginal specimens should be evaluated in the near future.